The right thalamic glutamate level correlates with functional connectivity with right dorsal anterior cingulate cortex/middle occipital gyrus in unmedicated obsessive–compulsive disorder: A combined fMRI and 1H-MRS study. (March 2019) - Chen, Yongjun; Meng, Ziyu; Zhang, Zongfeng; Zhu, Yajing; Gao, Rui; Cao, Xuan; Tan, Ling; Wang, Zhen; Zhang, Haiyin; Li, Yao; Fan, Qing
Objective: The imbalance in neurotransmitter and neuronal metabolite concentration within cortico-striato-thalamo-cortical (CSTC) circuit contributes to obsessive–compulsive disorder's (OCD) onset. Previous studies showed that glutamate mediated upregulation of resting-state activity in healthy people. However, there have been few studies investigating the correlational features between functional and neurochemical alterations in OCD. Methods: We utilize a combined resting-state functional magnetic resonance imaging (rs-fMRI) and proton magnetic resonance spectroscopy ( 1 H-MRS) approach to investigate the altered functional connectivity (FC) in association with glutamatergic dysfunction in OCD pathophysiology. Three regions of interest are investigated, i.e., medial prefrontal cortex and bilateral thalamus, for seed-based whole-brain FC analysis as well as MRS data acquisition. There are 23 unmedicated adult OCD patients and 23 healthy controls recruited for brain FC analysis. Among them, 12 OCD and 8 controls are performed MRS data acquisition. Results: Besides abnormal FC within CSTC circuit, we also find altered FCs in large-scale networks outside CSTC circuit, including occipital area and limbic and motor systems. The decreased FC between right thalamus and right middle occipital gyrus (MOG) is correlated with glutamatergic signal within right thalamus in OCD patients. Moreover, the FC between right thalamus and right dorsal anterior cingulate cortex (dACC) is associated with glutamate level in right thalamus, specifically in patient's group. Finally, the FC between right thalamus and right MOG is correlated with patient's Yale–Brown Obsessive Compulsive Scale (YBOCS) compulsion and total scores, while the right thalamic glutamatergic signal is associated with YBOCS-compulsion score. Conclusion: Our findings showed that the coupled intrinsic functional–biochemical alterations existed both within CSTC circuit and from CSTC to occipital lobe in OCD pathophysiology.